An Efficient Secure and Privacy Cloud Auditing in Winternitz Signature Scheme - Mageshwari, M.; Naresh, R. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This cloud computing approach gives customers access to many platforms and delivers scalable, on-demand services whenever and wherever they are needed. The main issues in an outsourcing approach occur because users no longer possess access and ownership of their data, which means it is more challenging to conduct appropriate security audits. Winternitz Signature Scheme (WSS) is an extremely important cryptosystem. Not only may many signatures be compressed into a shorter signatures, but also guarantee the authenticity of each signature taking part in the combination by checking if the resultant aggregate signature is valid. Cloud server, Third Party Audit (TPA), and Data owners providers are all needed to complete the service. For the data owner, these processes include dividing the blocks in file, each encrypts of them, calculating a hash key, then merging them back together to produce a signature, and finally transmitting the result. The new audit method has used to cope with all these requirements. In this approach, the cloud server maintains a verifiable secure signature scheme, allowing for batch auditing. When it comes to practical arrangements, the efficiency and security of our approach are shown by the fact that it is reducing the computing and communication auditing process cost, which is particularly beneficial.